„ГРАЖДАНИН МИРА” КАК КАТЕГОРИЯ И КАК ОБРАЗ РУССКОЙ ЛИТЕРАТУРЫ - ПОДЧИНЕНОВ, АЛЕКСЕЙ; СНИГИРЕВА, ТАТЬЯНА (Studia Rossica Posnaniensia, 2006)
The article considers a social and political category of the citizen o f the world as a base of the hero typology in Russian literature of the 19-th and 20-th centuries. The main attention is given to transformation of traditional fiction images (the unnecessary man, the Russian European, the Russian wanderer, etc.) during this period. It results in the replacement of the concept of the citizen o f the world with the concept the person of the world.